Analysis of Aerobic Endurance (VO2Max) in the Physical Condition of Orynity Palu Futsal Club - Daipaha, Moh. Tris Maulana; Lumbaa, Krisyanto Batong; Rivalwan, Rivalwan; Saldi, Muh.; Primadana, Ryo Sinung (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. This study aimed to assess the physical condition of athletes from the Orynity Palu futsal club, specifically focusing on their aerobic endurance, measured by VO2Max. Materials and methods. The participants in this study consisted of 14 individuals, all of whom were athletes or futsal players from the Orynity Palu club. This investigation was carried out through the implementation of a bleep test or MFT. This study is a descriptive investigation, aimed at assessing the aerobic endurance physical condition of the Orynity Palu futsal club as it currently stands, without any prior intervention. Results. Data analysis reveals that the average aerobic endurance, or VO2Max, for the Orynity Palu futsal club is 40.8, which falls into the moderate category. Within this assessment, 8 individuals, representing 57.14%, are classified in the good category, 5 individuals, or 35.71%, are in the medium category, and 1 individual, accounting for 7.14%, is in the poor category. Conclusion. The findings of the study indicate that the aerobic endurance (VO2Max) of the players from the Orynity Palu Futsal Club falls within the good category. The implemented training has demonstrated effectiveness, yet certain areas require enhancement. The findings presented here may serve as a valuable reference for the development of a more effective training program.